Legal disputes in determining the religion of the child when one parent converts to Islam under Malaysian Law - Mohd Zin, Najibah; Che Soh @ Yusoff, Roslina (INSI Publications, 2012)
This paper examines the child’s right to determine his / her religious status when one parents converts to Islam under Malaysian law. Determination as to the religious status of a child as well as custodial rights are very much in dispute between these parents as their marriage has to come to an end due to religious sanctions and lack of tolerance between them to come to a settlement. As opposed to custodial right, the issue is whether the welfare principle is still relevant in determining the religious status of a child. The current practice suggests that the father is the central focus in deciding the child’s religion under the Federal Constitution as well as Shari‘ah rules though lately there were arguments to allow both parents to have such power. Therefore this study will examine legal provisions pertaining to children’s right to religion under Malaysian law and explore an equal position under the Shari‘ah.